Pengaruh Implementasi SIGA dan Kompetensi Digital Terhadap Efektivitas Kerja Pegawai Perwakilan BKKBN Provinsi Sulawesi Barat - Badani, M. Iqbal; Ramli S, Ramli S; Aqil, Muhammad; Dahri, Nur Wahyunianti (Pascasarjana Universitas Muhammadiyah Mamuju, 2025)
This study aims to examine the extent to which the implementation of SIGA and employees' digital competence influence work effectiveness within the Representative Office of BKKBN in West Sulawesi Province. A quantitative approach was employed, involving a sample of 101 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that both independent variables have a positive and significant effect on work effectiveness (significance value = 0.000). The findings reveal that an improvement in SIGA implementation contributes to a 0.290-point increase in work effectiveness, while enhanced digital competence has a greater impact, contributing 0.423 points. The coefficient of determination (R²) of 0.633 indicates that approximately 63.3% of the variance in employee work effectiveness can be explained by the combination of the two variables. Among them, digital competence emerges as the most dominant factor, as reflected by its higher standardized beta value compared to SIGA implementation